EFEK RESIDU VERMIKOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG (Ipomoea reptans Poir) SELAMA TIGA PERIODE PENANAMAN SECARA HIDROGANIK - burhanudin firdaus; Nurhidayati Nurhidayati; Abdul Basit (AGRONISMA, 2020)
Hydroganic is a hydroponic planting system that uses organic fertilizers, one of which is vermicompost, which is a high-quality organic fertilizer derived from an overhaul of organic material by earthworms that contain high enough nutrients so that it can provide residual effects on subsequent plants. This study aims to determine how long the effect of vermicompost residue can provide optimum productivity in hydroganic media. The experiment was carried out using a factorial randomized block design (RCBD) with control using 2 factors. The first factor is the vermicompost application method (100% solid vermicompost, 50% solid vermicompost 50% liquid vermicompost, 100% liquid vermicompost) and the second factor is a vermicompost dose of 100-500 g / polybag. The parameters observed were plant height, number of leaves, fresh weight of plantations, fresh weight per plant, dry weight per plant, dry weight per plant. the results of this study showed that the best yield was in the M1V4 treatment (100% solid Vermicompost at a dose of 400 g / polybag) with an average yield of fresh weight per polybag 178.27 g (first planting period). There was a decrease in production over the three planting periods in M1 treatment production decreased by 25.29% (residual effect 1), 36.05% (residual effect 3), and 52.22% (third residual effect). In the M2 treatment, it was 4.40% (residual effect 1), 23.44% (residual effect 2), and 26.82% (residual effect 3) and in M3 treatment there was a decrease of 19.19% (residual effect 1), 28.19 (residual effect 2), and 41.98 (residual effect 3).